2006
DOI: 10.1186/1471-2474-7-32
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of unprocessed and photooxidized bovine and human osteochondral grafts in collagen-sensitive mice

Abstract: Background: Autologous and allogeneic osteochondral grafts have been used to repair damaged or diseased cartilage. There are drawbacks to both of these methods, however. Another possible source for osteochondral grafting is photooxidized xenograft scaffolds. The purpose of this study was to evaluate the adaptive immune response to unprocessed and photooxidized xenogeneic osteochondral grafts in a collagen-sensitive mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is well demonstrated that type II collagen, isolated, induced high titles of IL2, IL4, IFN-gama and specific IgG and IgM (Kawalec-Carroll et al 2007). Certainly due to the alterations that this protein exhibits after treatment, specific imunoglobulins against type II collagen had not been detected in the serum of rats that received frozen bone or bone submitted the photo-oxidation.…”
Section: Discussionmentioning
confidence: 94%
“…It is well demonstrated that type II collagen, isolated, induced high titles of IL2, IL4, IFN-gama and specific IgG and IgM (Kawalec-Carroll et al 2007). Certainly due to the alterations that this protein exhibits after treatment, specific imunoglobulins against type II collagen had not been detected in the serum of rats that received frozen bone or bone submitted the photo-oxidation.…”
Section: Discussionmentioning
confidence: 94%
“…The main problem associated with the application of collagen and its derivatives as bone fillers comes from the intrinsic immunogenicity of the collagen molecule, 279 namely, most of it is xenogenic in origin because it is difficult to obtain directly from a patient, and recombinant technologies and the methods to extract the immunogenic, telopeptide portion of collagen molecules are not only of limited availability but also lead to reduced bioactivity of the protein. 280 Although collagen has been successfully applied topically, for example, in biodegradable sutures and as a prophylactic wound dressing carrier of antibiotics, 281283 its mere subcutaneous epithelialization may lead to undesired immunogenic or antigenic responses.…”
Section: Advanced Drug Delivery Platforms In the Research Stagementioning
confidence: 99%
“…The second problem associated with the application of collagen as a component of bone fillers comes from its intrinsic immunogenicity 56 , a direct consequence of the fact that it is difficult to obtain directly from the patient and that most of it is xenogeneic in nature, while recombinant technologies as well as the methods to extract the immunogenic, telopeptide portion of collagen molecules are not only of limited availability, but also lead to reduced bioactivity of the protein 57 . The products of its degradation in vivo , the rate of which is often very variable, depending on the concentration of immunologically activated collagenases in the extracellular matrix surrounding the implant, have frequently been observed to lead to fibrous capsule formation 58 .…”
Section: Collagen/apatite Composites Modeled After the Structure Omentioning
confidence: 99%